Network data analysis in improving pedagogical supervision with software webQDA - Sá, Susana (2021)
Qualitative research has increasingly complex research objects and thus the work of analysing and treating corpora data are increasingly more demanding for a single researcher. Therefore, the use of collaborative work among several researchers becomes more and more relevant. The Computer Assisted Qualitative Data Analysis Software (CAQDAS) solutions, namely the webQDA® software, have made this online collaboration easier. The problem of research is the perception of the practice of the collaborative process in content analysis with the help of CAQDAS (webQDA®) software. Three self-reflections were analysed and treated (three Narratives) by three master’s students of pedagogical supervision, who categorized 2301 observation narratives of classes in higher education. The content analysis was handled using webQDA® software. From the emerging categories, it was concluded that: a) time is a factor to be taken into account in the collaborative work, as it reduced the categorization time and b) it is possible to consolidate learning in the qualitative research. This work, despite having a great limitation - a very small sample - serves as a future pedagogical suggestion in order to improve Pedagogical Supervision classes, making them more fruitful, using the collaborative work of webQDA® software in order to increase, in a timely manner, the skills and competences of qualitative researchers in the students.